2019
DOI: 10.1159/000501645
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Stress-Reducing Interventions on the Response to Challenges to the Immune System: A Meta-Analytic Review

Abstract: <b><i>Background:</i></b> There is consistent evidence showing an interplay between psychological processes and immune function in health and disease processes. <b><i>Objectives:</i></b> The present systematic review and meta-analysis aims to provide a concise overview of the effectiveness of stress-reducing psychological interventions on the activation of immune responses in both healthy subjects and patients. <b><i>Methods:</i></b> Inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 111 publications
1
29
0
3
Order By: Relevance
“…Though compared to flow cytometry for the identification of PBMC subpopulations, the determination of cytokines in cell culture supernatants can be done with comparably smaller effort. Future studies in this vein could establish this more complex but highly instructive analysis side by side with more easily applicable protocols to determine hyper-reactivity of the immune system to challenge in the clinic, for example by using skin tests ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though compared to flow cytometry for the identification of PBMC subpopulations, the determination of cytokines in cell culture supernatants can be done with comparably smaller effort. Future studies in this vein could establish this more complex but highly instructive analysis side by side with more easily applicable protocols to determine hyper-reactivity of the immune system to challenge in the clinic, for example by using skin tests ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Psychological interventions have been shown to be effective in improving self-reported health outcomes [ 1 , 2 ] and immune status [ 3 - 5 ]. Two meta-analytic reviews found modest support for improved immune function after psychological interventions [ 6 , 7 ]. However, it is difficult to draw conclusive findings from these studies due to the large heterogeneity in the incorporated interventions (ie, various types of relaxation, conditioning, disclosure, and stress management interventions) and immunological outcomes (ie, quantitative and qualitative).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to draw conclusive findings from these studies due to the large heterogeneity in the incorporated interventions (ie, various types of relaxation, conditioning, disclosure, and stress management interventions) and immunological outcomes (ie, quantitative and qualitative). Moreover, novel developments in psychological treatments may potentially further enhance the effectiveness of psychological interventions in improving self-reported and immunological health outcomes [ 7 ]. A rather novel development focuses on providing psychological interventions based on cognitive behavioral therapy (CBT) via the internet (ICBT).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations